ANALISIS HUBUNGAN KARAKTERISTIK PERAWAT TERHADAP KEMAMPUAN NON TEKNIS DALAM PELAKSANAAN KEGAWATAN NEONATAL - Ni Luh Diah Ayu Sita Dewi; Ali Haedar, Ahsan (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2017)
Abstract : The ratio of neonatal mortality rate increases with the number of births. The quality of the emergency of neonatal treatment with adequate facilities supported capacity of health personnel in the management of neonatal emergency is very important. Emergency nurse competence consists of: cognitive, clinical skills, and non-technical skills. Non-technical skills or soft skills, namely: communication, teamwork, situation awareness, leadership and decision-making and stress management. They still lack the training and learning curriculum non technical capability in the handling of the emergency of neonatal into inaccuracies in implementing the emergency of neonatal handling competence. Characteristics demographic is very influential in the implementation of the competence and performance of the emergency of neonatal nurses. The aim of this research is to analyze the characteristics of nurses to non technical capabilities in the implementation of the emergency of neonatal health center PONED. The design was cross-sectional sampling using purposive sampling technique. The number of study subjects consisted of 153 respondents. Instruments used in the form Closed Ended instrument. Based on the test results with Cross Table p value p> 0.05 characteristics of the training and continuing education, long work experience, and employment status of nurses is not related to the ability of non-technical nurses. Characteristics middle adulthood, the sex of male nurses (p <0.05) related to the non-technical abilities of nurses though not significant. Characteristics of respondents with education level S1 nursing significantly related to non technical capabilities of nurses in the decision-making capability variables. The conclusion of this study is characteristic of primary education nursing nurses correlate significantly on the ability of non-technical in neonatal emergency handler. Nursing implications of this research are expected to be upgraded non-technical ability to repair competence in the handling of the emergency of neonatal nurses.Keywords : demographics, skills, neonatal, non-technical, emergency, nurse Abstrak : Rasio angka mortalitas neonatal meningkat seiring peningkatan jumlah kelahiran. Kualitas penanganan kegawatan neonatal dengan fasilitas memadai ditunjang kemampuan tenaga kesehatan dalam penanganan kegawatan neonatal sangat penting. Kompetensi perawat kegawatan terdiri dari : kognitif, keterampilan klinis, dan keterampilan non teknis. Keterampilan non teknis atau soft skill yaitu :komunikasi, kerjasama tim, kesadaran situasi, kepemimpinan, pengambilan keputusan, dan manajemen stres. Masih minimnya pelatihan dan kurikulum pembelajaran kemampuan non teknis dalam penanganan kegawatan neonatal menjadi ketimpangan dalam melaksanakan kompetensi penanganan kegawatan neonatal. Karakteristik demografi sangat berpengaruh dalam pelaksanaan kompetensi dan performa perawat kegawatan neonatal. Tujuan dari penelitian ini menganalisis karakteristik perawat terhadap kemampuan non teknis dalam pelaksanaan kegawatan neonatal di Puskesmas PONED. Desain yang digunakan adalah cross sectional dengan teknik sampling menggunakan purposive sampling. Jumlah subyek penelitian terdiri dari 153 responden. Instrumen yang digunakan berupa Closed Ended Instrumen. Berdasarkan hasil uji dengan Cross Table nilai p value p>0.05 karakteristik pelatihan dan pendidikan lanjut, lama pengalaman kerja, dan status kepegawaian perawat tidak berhubungan terhadap kemampuan non teknis perawat. Karakteristik usia dewasa pertengahan, jenis kelamin laki-laki perawat (p<0,05) berhubungan terhadap kemampuan non teknis perawat walau tidak signifikan. Karakteristik responden dengan tingkat pendidikan S1 keperawatan berhubungan secara signifikan terhadap kemampuan non teknis perawat pada variabel kemampuan pengambilan keputusan. Kesimpulan dalam penelitian ini adalah karakteristik pendidikan dasar keperawatan perawat berhubungan secara signifikan terhadap kemampuan non teknis dalam penanganan kegawatan neonatal. Implikasi keperawatan dalam penelitian ini adalah diharapkan kemampuan non teknis ditingkatkan untuk perbaikan kompetensi perawat dalam penanganan kegawatan neonatal. Kata kunci : demografi, ketrampilan, neonatal, non teknis, kegawatan, perawat